2021
DOI: 10.1073/pnas.2021091118
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-metabolizing gut microbes regulate adult neurogenesis via the aryl hydrocarbon receptor

Abstract: While modulatory effects of gut microbes on neurological phenotypes have been reported, the mechanisms remain largely unknown. Here, we demonstrate that indole, a tryptophan metabolite produced by tryptophanase-expressing gut microbes, elicits neurogenic effects in the adult mouse hippocampus. Neurogenesis is reduced in germ-free (GF) mice and in GF mice monocolonized with a single-gene tnaA knockout (KO) mutant Escherichia coli unable to produce indole. External administration of systemic indole increases adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 96 publications
0
73
0
Order By: Relevance
“…Recently, Wei et al investigated the effect of indole, a tryptophan metabolite of colonic microbiota, on hippocampal neurogenesis, and showed that the neurogenic effect was mediated by the aryl hydrocarbon receptor (AhR) [142]. In that study, however, another AhR ligand, kynurenine, did not induce neurogenesis, suggesting ligand specificity in the AhR-mediated regulation of neurogenesis.…”
Section: Maintenance Of Bdnf Expression and Neurogenesismentioning
confidence: 99%
“…Recently, Wei et al investigated the effect of indole, a tryptophan metabolite of colonic microbiota, on hippocampal neurogenesis, and showed that the neurogenic effect was mediated by the aryl hydrocarbon receptor (AhR) [142]. In that study, however, another AhR ligand, kynurenine, did not induce neurogenesis, suggesting ligand specificity in the AhR-mediated regulation of neurogenesis.…”
Section: Maintenance Of Bdnf Expression and Neurogenesismentioning
confidence: 99%
“…Indeed, it can be inferred that AHR may influence viral infection through impacting IRF-3 independent of IFN. Interestingly, gut and skin microbes regulate neurogenesis and skin barrier function via AHR signaling in mice based on mice lacking AHR having neurogenesis dysfunction and being more liable to infection ( 31 , 32 ), suggesting the existence of an opposite role of this receptor when infected with different microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in mice under chronic mild stress observed that indole production correlated with changes in mice behavior (Mir et al, 2020), while overproduction of indoleinduced anxiety-like behavior in rats (Jaglin et al, 2018). In contrast, studies in mice have shown that indole stimulation of the AhR regulates neurogenesis in the adult hippocampus, a critical step in recovering from depression (Wei et al, 2021). Thus, maintenance of indole levels appears critical for proper gutbrain axis regulation (Jaglin et al, 2018;Mir et al, 2020).…”
Section: Biosensors For the Detection Of Gut-brain Axis Dysregulation...mentioning
confidence: 97%